A4.6 Effects of Cholic Acid and its Derivatives in Experimental Arthritis. (25th February 2013) - Hayer, Silvia; Halilbasic, Emina; Niederreiter, Birgit; Willburger, Martin; Mandl, Peter; Saferding, Victoria; Blüml, Stephan; Smolen, Josef; Trauner, Michael; Redlich, Kurt
Abstract : Introduction: Bile acids play an important role in cholesterol metabolism and act as intestinal detergents for digestion and absorption of fats and fat-soluble vitamins. Disruption of bile flow causes cholestatic liver diseases. Derivatives of cholic acid (CA) such as nor-ursodeoxycholic acid (norUDCA) are promising therapeutic agents in the treatment of cholangiopathies. Previous studies also demonstrated anti-inflammatory and anti-fibrotic properties of norUDCA in experimental sclerosing cholestasis. Objective: To investigate the anti-inflammatory potential of CA and its derivatives ursodeoxycholic acid (UDCA) and nor-UDCA in in Collagen-induced arthritis (CIA), an animal model for inflammatory, erosive arthritis. Methods: Mice were prophylactically treated with CA, UDCA or nor-UDCA enriched diet pellets (5 mg/kg diet) or standard diet pellets (Placebo) ad libitum starting 1 week before the first immunisation with collagen. Animals were weekly assessed for clinical signs of arthritis, body weight and food consumption during the experimental period. After 10 weeks of treatment hind paws, liver, sera and lymph nodes were isolated for further analysis. Sera were investigated for anti-collagen antibodies, cytokine responses and liver parameters such as alkaline phosphatase (AP) and alanine transaminase (ALT). Paraffin-sections of hind paws were examined for histoptahological changes in synovial inflammation, subchondral bone erosion, cartilage damage and osteophyte formation. Cell populations within synovial pannus were identified by immunhistochemical stainings and were determined using HistoQuest software (from TissueGnostics). Results: Uptake of CA, UDCA and norUDCA was confirmed by serum analysis. Prophylactic treatment of CIA mice with UDCA and norUDCA could not significantly prevent disease incidence. In contrast, treatment with CA led to a marked increase in disease incidence and severity compared to Placebo treated animals. Whereas UDCA and norUDCA showed a similar course of clinical signs of arthritis. Histological analysis of hind paws revealed an increase in synovial inflammation, bone erosion and cartilage damage in the CA treated animals compared to the Placebo group. No changes in joint pathology were observed in the UDCA or norUDCA treated group. Despite differences in absolute numbers of infiltrating cells, immunhistochemical staining for cell specific markers demonstrated no markedly changes in the distribution of neutrophils, macrophages, T- and B-lymphocytes within inflammatory synovial tissue. Similar amounts of total anti-collagen IgG and its subtypes IgG2 and IgG2c were found in all treatment groups. Moreover, FACS analysis of lymph node cells revealed similar amounts of T-cells, B-cells, dendritic cells and macrophages. In contrast, serum analyses revealed a trend toward increased IL-6 levels suggesting that CA exacerbates IL-6 levels driving disease onset and severity in CIA model. Conclusions: Bile acid derivatives UDCA and norUDCA could not modulate collagen-induced arthritis. In contrast, cholic acid (CA) exacerbated the incidence and severity of inflammatory, erosive arthritis in this model. Thus, promising anti-inflammatory and anti-fibrotic agents for cholangiopathies have therefore no beneficial effects in an experimental arthritis model.